Improving the allocation of junior doctor resources using a Pareto analysis of pager activity - Khan, Afroze S.; Biggs, Timothy C.; Faoury, Morad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Pareto analysis is the cornerstone of most businesses improvement strategies around the world. It has been used in healthcare as part of quality improvement endeavours. Pager activity can be used as a surrogate to assess the sources and frequency of demands on junior doctor resources. Thus our aim is to analyse and improve the allocation of junior doctor resources through the study of pager calls using the Pareto principle. Methods: Retrospective observational study examining pager calls to Ear, Nose & Throat junior doctor/residents at the University Hospital Southampton, a tertiary referral centre on the south coast of the United Kingdom. A Pareto principle analysis was undertaken, assessing whether the majority of activity stems from a minority of sources. Results: In total, 2853 pager calls were included, averaging 31 pages a day over a three-month period. Highest daily page activity occurred at 11 am and 2 pm. Data conformed to the Pareto principle; 80% of activity came from 22% of sources, with the paediatric department providing the highest demand. Conclusions: Analysis of pager frequency data has shown confirmation to the Pareto principle, identifying that the majority of calls to the junior doctor/resident originate from a limited number of departments/locations. Such analysis has allowed a restructuring of resources, to better streamline departmental efficiency. A broader appreciation and adoption of Pareto analysis within the healthcare sector would enable improved resource allocation, in an era of limited healthcare budgets.